Utilization of an Intraoperative Grading Scale in Laparoscopic Cholecystectomy: A Nepalese Perspective - Suman Baral; Raj Kumar Chhetri; Neeraj Thapa (Gastroenterology Research and Practice)
Introduction. Difficult geographic diversity and late presentation to medical attention often make the laparoscopic cholecystectomy difficult and chances of conversion and complication remains. Various preoperative grading scales have been developed for predicting the difficulty of surgery in cholecystitis patients; however, intraoperative assessment of anatomical status and inflammation of the gall bladder has not been assessed till date except for some guidelines like the Parkland grading scale (PGS). We aimed to utilise this guideline in patients undergoing laparoscopic cholecystectomy in rural community of the developing nation. Methods. PGS was applied for all the patients undergoing laparoscopic cholecystectomy and laboratory and outcome factors like preoperative white blood cells (WBC), open conversion, subtotal cholecystectomy, length of surgery, and bile leaks postoperatively were assessed. Results. Among 178 patients who underwent cholecystectomy, there were 40 grade one GBs, 90 grade two GBs, 26 grade three GBs, 16 grade four GBs, and six grade five GBs. With a conversion rate of 6.74%, eight patients underwent subtotal cholecystectomy. Among them, four patients were graded as 5th grade, two as 4th grade, and two as 3rd grade according to PGS system. Postoperative bile leak was seen in three patients among which two were grade five GBs and one was grade four. Preoperative WBC, conversion to open, subtotal cholecystectomy, length of surgery, and postoperative bile leak all significantly increased with increasing grades (p<0.05). Conclusion. PGS can be applied in patients undergoing laparoscopic cholecystectomy in the rural setting of a developing nation. With its application, postoperative course could be predicted and adequate counselling can be done about the possibilities of the outcome.